GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 21863 species occurrences available in GBIF matching the query: TaxonKey: 872 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 21863 records from 60 constituent datasets: 6 records from Individual Sightings. 2 records from KU Museum of Invertebrate Paleontology. 252 records from Museum Victoria provider for OZCAM. 41 records from Iziko. 2 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 6 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 21 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 1 records from KNWR Entomology Collection. 433 records from iNaturalist research-grade observations. 2 records from Donnees ONF Faune-Flore-Fonge. 644 records from Geographically tagged INSDC sequences. 17 records from naturgucker. 12520 records from Western Australian Museum provider for OZCAM. 8 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 101 records from CNAN/Escorpiones Estado de Mexico. 5 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 8 records from Macaulay Library Audio and Video Collection. 1 records from UAM Insect Collection (Arctos). 43 records from Collection Arachnida - ZSRO. 4 records from IndOBIS, Indian Ocean Node of OBIS. 419 records from Arácnidos de Centroamérica. 3 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 16 records from Collection Arachnida - SNSD. 8 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 849 records from CNAN/Scorpiones. 142 records from Invertebrate Paleontology Division, Yale Peabody Museum. 126 records from Queen Victoria Museum Art Gallery provider for OZCAM. 86 records from Instituto de ciencias naturales. 74 records from Tasmanian Museum and Art Gallery provider for OZCAM. 2 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 2 records from NCSM Invertebrates Collection. 113 records from OEH Atlas of NSW Wildlife. 126 records from Illinois Natural History Survey Insect Collection. 8 records from Paleobiology Database. 2 records from Arachnida del Museo de Entomología de la Universidad del Valle. 150 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 727 records from Queensland Museum provider for OZCAM. 5 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 45 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1 records from Essig Museum of Entomology. 1 records from Biological and palaeontological collection and observation data MNHNL. 192 records from CAS Entomology (ENT). 1 records from Entomology at ZMUC, Natural History Musem of Denmark. 570 records from Australian National Insect Collection. 183 records from Occurrences in SinBIOTA. 1 records from CU Invertebrate Paleontology. 10 records from NMNH occurrence DwC-A. 100 records from Northern Territory Museum and Art Gallery provider for OZCAM. 975 records from Australian Museum provider for OZCAM. 525 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 788 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 2 records from Données ONF Faune-Flore-FOnge. 21 records from Collection Arachnology SMF. 2 records from Recent Invertebrates Specimens. 238 records from Colección de artrópodos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 207 records from Museum of Comparative Zoology, Harvard University. 366 records from Especímenes INBio. 1 records from SysTax - Zoological Collections. 648 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 11 records from invertebratezoology.
Keywords: GBIF; biodiversity; species occurrences